The wedding singer - Coraci, Frank; Sandler, Adam.; Barrymore, Drew.; Taylor, Christine, 1971- (Burbank, CA : New Line Home Entertainment : Warner Home Video (distributor), 2006)
Robbie Hart is a wedding singer who can cover the latest hits, deliver the perfect toast to the bride and groom and even get Grandma on the dance floor. But when Robbie is dumped at his own wedding, he has a total eclipse of the heart and becomes the ultimate cynic. It's not until he meets Julia, a waitress, that Robbie starts to come around. However, Julia's about to get married herself, and unless Robbie can pull off the performance of a lifetime, the girl of his dreams may be gone forever.
Title from container.
Originally released as a motion picture in 1998.
Special features: More primo footage than before; "'80s mix tapes"; jump to a song feature; "A backstage look at 'The wedding singer' on Broadway" featurette.
Director of photography, Tim Suhrstedt ; production designer, Perry Blake.
Adam Sandler, Drew Barrymore, Christine Taylor.
DVD, region 1, widescreen (1.85:1) presentation; Dolby digital 5.1 surround, DTS surround, Dolby Digital stereo.